Determinación de incidencia de la relación carbono: nitrógeno en la producción de biomasa y ácidos grasos de la microalga chlorella vulgaris a escala de laboratorio (2014)
Sought to establish the effect of varying the carbon: nitrogen ratio in the production of biomass and fatty acids in the microalgae Chlorella vulgaris, using liquid foliar fertilizer as culture medium and control medium. Three different Carbon: Nitrogen ratios (1:1, 1:5 and 15:1) were evaluated compared with control medium at laboratory scale. Cell concentration was assessed by growth curves over 15 days. The biomass obtained after sequential processes sedimentation, centrifugation and lyophilization was evaluated in terms of performance, with the best for the 15:1 ratio (0.71 g/L). Finally, it was determined that the concentration of nitrogen in the growth medium altered fatty acid composition produced by significantly microalgal cells by analysis of lipid profile obtained by gas chromatography.